Slotted series Iteration log periodic fractal koch antenna with stub-loaded for UHF TVWS applications - Nur Akmal Abd. Rahman (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2016)
The main objectives of this research work are as follows to design and fabricate log periodic dipole array (LPDA) antenna for UHF TVWS (0.47-0.79 GHZ). To miniaturize size of LPDA antenna by using series iteration of fractal Koch and titled slot technique. To investigate the effect of stub on proposed slotted series iteration log periodic fractal Koch antenna (S-LPFKA).